(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This study explored social theatre as a means for the re-education, reintegration, and identity awareness of inmates at Las Palmas I Penitentiary Center (Gran Canaria, Spain), through focus groups with 15 men (24-55 years) who participated in the creation and performance of Atrapasueños, a play based on their personal experiences. Experiences, challenges, the creative process, family impact, and future reflections were analyzed using inductive analysis with Nvivo, from which seven key categories emerged. The results show that social theatre enabled them to rewrite their lives, process trauma, and envision positive alternatives.